The Impact of Social Entrepreneurship Efforts against Child Abuse - Naidoo, Nadine (My University, 2011)
Problem: Child pornography has grown from isolated and opportunistic paedophile attacks on children to a cybercrime war of terrorism claiming the lives of children and babies no more than a few weeks old. To sustain this multi-billion dollar child pornography industry and an insatiable paedophile and pornography consumer population, children around the world are exploited in the converging online and offline environment using simple technologies to produce made-to-order child sexual abuse images and pay-per-view live-streaming abuse. Purpose of the research: The study aims to understand the nature of global solutions that exist to fight the child pornography industry in order to scale proven solutions to South Africa. Methodology: The study follows a qualitative approach using in-depth interviews with 15 experts in the field of child protection in the United States, Canada and the United Kingdom. The sample comprises innovators and alliance partners in the corporate, NGO or government sectors. Three questions posed are: 1) What is the nature of the child pornography industry? 2) How are innovations to fight child pornography social entrepreneurial in nature? 3) What strategies are used to scale innovations to fight child pornography? The conclusions are then applied to the South African and African context. The key findings: The ecosystem analysis of the growth of the child pornography industry across the US, UK and Canada reveals consistent environmental conditions (political, economic, geographic, infrastructure and culture), stakeholders (resource providers, beneficiaries, allies, complementary organisations, competitors and opponents) and evidence of negative social impact. Second, the innovations are found to be social entrepreneurial in nature as they are guided by compelling social impact theories. Third, the innovations have been successfully scaled from the US, UK and Canada to Europe, Asia and Australia. These innovations could disrupt Africa‟s rape culture and protect children if scaled into the continent successfully.
MBA - WBS
Keywords: Child abuse; Social entrepreneurship; Child pornography